Implementasi pendidikan akhlak dalam keluarga di desa Tanimulya, Ngamprah, kabupaten Bandung Barat - Yelis Nur Wahidah; Hanifah; Muhamad Lutfi Assidiq; Hana Fauziah (At Turots: Jurnal Pendidikan Islam, 2023)
The family environment is the initial phase of education that greatly influences the formation of children's morals. The position of morality in human life occupies a very important position, because the good or bad of a person depends on how he behaves. In the family, parents are role models in morals. If the parents set a good example, the child will be good, but on the other hand, if the parents only set a bad example, the child will imitate bad behavior. This study aims to determine the implementation of moral education in the family in Tanimulya Village, Ngamprah District, West Bandung. This research uses field research (field research). The analysis uses descriptive qualitative data collection techniques through observation, interviews and documentation. The results of the study were that the implementation of moral education in the family in Tanimulya village was carried out well, the parents had applied good morals to the family, especially their children. This can be seen in the behavior of the children of Tanimulya Village. For example, when entering the house and leaving the house, you are used to greeting and kissing your hands, eating and drinking with your right hand while sitting.